Comparative Evaluation of Profitability Determinants : Evidence of Non-Finance Versus Finance Firms - Muhammad Muhaizam, Musa (2005)
The purpose of this study is to investigate factors that affect the profitability determinants on firms listed on the Bursa Malaysia Main Board. This study covers a period from 1999 to 2004 with 60 firms selected across six sector of economy in Malaysia. The objectives of this study are firstly to find out the factors affecting profitability of the overall sectors selected in this study; secondly to differentiate the significant profitability determinants of finance sector and non-finance sector of the Malaysian economy. The third objective is to investigate the different sectors influence on the profitability of firms. All results are tested at 0.05 significant levels. To achieve the objectives, multivariate regression is used to test the hypothesis. From the analysis, the result suggest that firm capital investment intensity, the leverage ratio, profit margin, asset turnover and industry capital intensity on all firms sample have significant impact on the profitability determinants. In contrast, firm sales growth and market share are not significantly related to the contribution on profitability determinants. On the other hand, the profitability determinants of nonfinance sector are affected by firm sales growth, profit margin, leverage ratio, firm capital investment intensity, asset turnover and industry capital investment intensity. For finance sector, firm size, profit margin, leverage ratio and asset turnover are the factors that contributed to profitability determinants. This study also indicated that different sectors’ effect is not significant in the determinations of profitability between finance sector and non-finance sector.